2015
DOI: 10.3111/13696998.2015.1109518
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of persistence, adherence, and health economic outcomes of fixed-dose combination vs loose-dose combination of oral anti-diabetes drugs

Abstract: Management of T2DM using FDC therapies provides a compliance benefit relative to LDC therapies that may translate to reductions in healthcare utilization and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…In a retrospective study, patients with type 2 diabetes treated with FDC had a low rate of non-persistence [7]. Drug adherence was reported to increase when patients were switched from LDC therapy with pioglitazone and metformin to analogous FDC therapy [8]. It was reported that treatment with FDC was associated with lower costs and increased possibility of achieving the target HbA1c in a retrospective study [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study, patients with type 2 diabetes treated with FDC had a low rate of non-persistence [7]. Drug adherence was reported to increase when patients were switched from LDC therapy with pioglitazone and metformin to analogous FDC therapy [8]. It was reported that treatment with FDC was associated with lower costs and increased possibility of achieving the target HbA1c in a retrospective study [12].…”
Section: Discussionmentioning
confidence: 99%
“…Many FDC regimens for hypertension are available in Japan, but only five for diabetes. In retrospective studies, switching from loose dose combination (LDC) therapy to FDC therapy improved adherence [7, 8]. In another retrospective study, the most recent HbA1c level of patients who took an FDC of DPP-4 inhibitor and metformin was lower than that of patients who took an LDC of DPP-4 inhibitor and metformin free form [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, data directly addressing the effects of antihyperglycemic SPCs with respect to health care costs are quite limited [82]. Some data suggest reduced health care utilization and costs with an SPC versus loose-pill regimens [11]—a paradox as many formularies penalize SPCs with higher prices. Prescribing an SPC limits dose flexibility, and thus many physicians prefer using them as a maintenance option rather than an initial therapy.…”
Section: Spc Therapymentioning
confidence: 99%
“…For example, insulins and sulfonylureas (SUs) are associated with weight gain and hypoglycemia [1], the latter being of particular concern in the elderly [10]. The management of T2DM may be facilitated with single-pill combinations (SPC) by enabling patients to take fewer pills per day, which may lead to improved patient adherence [11]. Many combinations include metformin and can be used early in the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, adherence to fixed-dose combinations of oral antidiabetic treatments is better than adherence to free drug combinations [7]. Not surprisingly, non-adherence to treatment is consistently associated with poorer glycemic control; HbA 1c levels are higher by 0.4-0.7% in nonadherent compared with adherent patients [4].…”
mentioning
confidence: 99%